In situ assessment of the liver microcirculation in mechanically ventilated rats using sidestream dark-field imaging - Černý, V; Turek, Z; Pařízková, R (Physiological research, 2009)
Assessment of hepatic microcirculation by on-line visualization has been impossible for a long time. Sidestream dark-field (SDF) imaging is a relatively new method allowing direct visualization of both mucosal microcirculation and surface layers microcirculation of solid organs using hand-held probe for direct contact with target tissue. The aim of this study was to evaluate the feasibility of studying the rat hepatic microcirculation in situ by SDF imaging. The liver lobes were left in situ, and images were obtained using SDF imaging on the surface of the liver via upper midline laparotomy. Images were captured intermittently during 10-sec apnoea and recorded. The microvascular parameters were compared with previous validation studies. Clear high contrast SDF images were successfully obtained. Quantitative analysis revealed a mean FSD (functional sinusoidal density) of 402+/-15 cm/cm(2), a sinusoidal diameter of 10.2+/-0.5 microm and postsinusoidal venular diameter of 33.9+/-13 microm. SDF imaging is a suitable noninvasive method for accurate quantification of the basic microcirculatory parameters of the liver in situ without a need to exteriorize the liver lobes. This method seems to be applicable in animal studies with possibility to use SDF imaging also intraoperatively, providing unique opportunity to study liver microcirculation during various experimental and clinical settings.
Keywords: potkani Wistar; zvířata; Male; Microcirculation; umělé dýchání; Feasibility Studies; reprodukovatelnost výsledků; Liver Circulation; Respiration, Artificial; Image Interpretation, Computer-Assisted; Animals; mužské pohlaví; krysa rodu Rattus; Rats; Microscopy, Polarization; Rats, Wistar; mikrocirkulace; studie proveditelnosti; Reproducibility of Results; interpretace obrazu počítačem; játra; jaterní oběh; Liver; polarizační mikroskopie